SELECTION OF MEDICAL SCHOOL/ROLE OF PAKISTAN MEDICAL AND DENTAL COUNCIL - Muhammad Akram Malik (Journal of University Medical & Dental College, 2020)
Medical Profession is highly respected and paying in the whole world, in civilized as well as developing countries. A large number of students are desirous of getting admission in medical schools, especially public medical colleges. In Punjab Pakistan, (largest province) around 47000 students appeared in entry test for admission in medical schools of province against only 3500 seats.